معالم السنن میں امام خطابیؒ کا منہج و اسلوب۔The methodology and stylistics of Maalim - U s - Sunan - شہزادہ عمران ایوب; ڈاکٹر محمد اعجاز (الإيضاح, 2013)
"The status of Ma'lim-us-Sunan is very high in explanations of Sunan Abu Dawood because it is considered first explanation of Sunan Abu Dawood. Imam Khattabi has adopted such a fine method in it that with the literal explanation of words and description of jurisprudential commandments he has also collected in it sayings of Salaf-us-Saalih, Arabian proverbs, different opinions of various scholars, grammatical rules and Jarh-o-ta'deel etc. To add, he, as a specially, Ahadith and quotations of Sahabah and scholars, has made provision to describe with his chain of narrators. Due to this, the book has adopted the basic primary status of Hadith knowledge. And further, because of these chains of narrators this book has adopted the form of reference source in matter of teachers identification of Imam Khattabi. Due to all these qualities undoubtedly the way this book was a need of scholars and researchers of every era, in the same way the scholars can never be exempted from this today."